2023
DOI: 10.3847/1538-4357/acbf46
|View full text |Cite
|
Sign up to set email alerts
|

CLASSY. VI. The Density, Structure, and Size of Absorption-line Outflows in Starburst Galaxies

Abstract: Galaxy formation and evolution are regulated by the feedback from galactic winds. Absorption lines provide the most widely available probe of winds. However, since most data only provide information integrated along the line of sight, they do not directly constrain the radial structure of the outflows. In this paper, we present a method to directly measure the gas electron density in outflows (n e ), which in turn yields estimates of outflow cloud prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…However, the lack of a clear correlation between v out and age in our sample does not allow us to apply a similar method in this work. The radii derived here are larger than the inner radii determined for the large-scale outflows in Chisholm et al (2016Chisholm et al ( , 2017 using photoionization models, while they overlap with the smaller sizes reported for the CLASSY sample (Xu et al 2023) using the nonresonant absorption lines.…”
Section: Challenges In the Measurement Of The Outflow Radiussupporting
confidence: 60%
“…However, the lack of a clear correlation between v out and age in our sample does not allow us to apply a similar method in this work. The radii derived here are larger than the inner radii determined for the large-scale outflows in Chisholm et al (2016Chisholm et al ( , 2017 using photoionization models, while they overlap with the smaller sizes reported for the CLASSY sample (Xu et al 2023) using the nonresonant absorption lines.…”
Section: Challenges In the Measurement Of The Outflow Radiussupporting
confidence: 60%
“…We present a uniform analysis of the Lyα profiles. The outflow properties have been determined from the blueshifted components of the LIS resonance lines (Xu et al 2022) and the excited fine-structure lines (Xu et al 2023). The results provide new insight into the clumpiness of the ISM, as described by the relative covering fractions of high-N H I and low-N H I gas, yet also strongly suggest that the discrepancies between shell-model parameters and LIS absorption lines arise from aperture vignetting.…”
Section: Introductionmentioning
confidence: 96%
“…As discussed in Section 2. scatter) increases at larger stellar masses, with only objects with M å  10 7 M e needing a two-component fit. We highlight here that all the galaxies characterized by a broad component in optical emission lines (apart Mrk 996 and SBS 0335-052 E) were found to have an outflowing component in rest-UV absorption lines analyzed by Xu et al (2022Xu et al ( , 2023 (CLASSY Paper III, Paper VI). Recent studies have shown that low-mass systems (M å < 10 9 M e ) such as those of the CLASSY survey can have irregular velocity fields in the ionized gas studied through optical emission lines, indicating the presence of noncircular motions (e.g., Marasco et al 2023).…”
Section: Discussionmentioning
confidence: 84%